(untitled) (Indian Journal of Animal Production and Management, 2018)
The present study was carried out to discriminate the prestanding, standing and end of standing heat conditions of estrus Sahiwal cows by observing their various physiological, haematological, blood biochemical attributes. The experiment was conducted on eight healthy, cyclic Sahiwal cows maintained at DDD farm of ILFC, DUVASU, Mathura. Out of various physiological and hematological parameters studied, a significant difference for three different stages of estrus in Sahiwal cows could be observed only for rectal temperature, PCV (P<0.01) and hemoglobin (P<0.05). During standing heat, the mean values for rectal temperature (39.00±0.10ºC), hemoglobin (12.45±0.20 mg/dl) and PCV (44.77±0.77 %) were found to be significantly higher than those during pre standing and end of standing heat stages. Interestingly, no significant difference for any of the bio chemical attributes in Sahiwal cows could be observed during three different stages of estrus, but few of the parameters viz. total protein, alkaline phosphatase, total immunoglobulin, albumin and calcium, significantly higher during standing heat as compared to other stages of estrus. This finding indicated that none of the bio- chemical attributes helpful in discrimination of the above said three stages of the estrus in Sahiwal cows.